Students’ Attitude Toward Digital Narrative Writing Project Based on Local Wisdom in EFL Classroom - Lisa Suhayati (ITScience (Information Technology and Science), 2025)
Writing is one of the most complex skills in English. The skill in organizing ideas into a paragraph or essay, and the skill of arranging grammatical sentences are also required. Nowadays, many teachers have implemented some media, techniques, and approaches to increase students’ motivation in writing classes. In the EFL classroom, teachers can also integrate writing with students’ cultural identity. This study investigates students’ perceptions of a digital narrative writing project based on local wisdom in an English as a Foreign Language (EFL) classroom. The writer applied a quantitative survey approach in this study, and the data were collected from participants who engaged in project-based digital narrative writing activities that combined local wisdom themes. The findings showed that students remarked on the digital narrative writing experience positively through four categories: affective (enjoyment and motivation), cognitive (learning benefits), cultural identity relevance, and technological usability. Students reported being more engaged, writing better stories, and feeling more connected to their culture. Even though some students had technical problems, most of them found the digital narrative writing project meaningful, creative, and useful for learning. The results show that the digital narrative writing project can improve students’ use of different media and support learning that connects to their culture in EFL classes. This has important meaning for how teachers design lessons, build digital skills, and include local culture in the curriculum.